Зарождение и развитие Харьковской школы теории управления - Бреславский, Дмитрий Васильевич; Горелова, Светлана Александровна; Ларин, Андрей Алексеевич (НТУ "ХПИ", 2006)
The paper is devoted to the genesis of Control Theory from first papers of Maxwell, Vyshnegradsky and Stodola. The contribution of Kharkiv engineers and scientists and the development of this Theory in control systems in power engineering and spacecraft technique are suggested
Keywords: теория центробежных регуляторов; автоматическое регулирование; аэрокосмическая отрасль; создание систем управления ракет-носителей; космические аппараты